2000
DOI: 10.1182/blood.v96.2.546
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of vascular endothelial growth factor receptor-3 in maintenance of integrity of endothelial cell lining during tumor angiogenesis

Abstract: Vascular endothelial growth factor (VEGF) plays a major role in tumor angiogenesis. VEGF-C, however, is thought to stimulate the growth of lymphatic vessels because an expression of its specific receptor, VEGF receptor-3 (VEGFR-3), was demonstrated to be restricted to lymphatic vessels. Here we demonstrate that the inactivation of VEGFR-3 by a novel blocking monoclonal antibody (mAb) suppresses tumor growth by inhibiting the neo-angiogenesis of tumor-bearing tissues. Although VEGFR-3 is not expressed in adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(45 citation statements)
references
References 32 publications
1
42
0
2
Order By: Relevance
“…Alitalo et al 40 showed that VEGFR-3 is involved in angiogenesis and growth of some tumors. Similarly, Kubo et al 41 have also reported that VEGFR-3 monoclonal antibody inhibits tumor xenograft growth in mice. Although it is not clear whether direct ligation and downstream signaling of VEGFR-3 can stimulate HA completely independent of VEGFR-2, it is clear through our studies that VEGFR-3 can directly functionally contribute to HA.…”
Section: Discussionmentioning
confidence: 82%
“…Alitalo et al 40 showed that VEGFR-3 is involved in angiogenesis and growth of some tumors. Similarly, Kubo et al 41 have also reported that VEGFR-3 monoclonal antibody inhibits tumor xenograft growth in mice. Although it is not clear whether direct ligation and downstream signaling of VEGFR-3 can stimulate HA completely independent of VEGFR-2, it is clear through our studies that VEGFR-3 can directly functionally contribute to HA.…”
Section: Discussionmentioning
confidence: 82%
“…Immunohistochemistry to detect VEGFR‐3 expression was performed as described with minor modifications (Kubo et al, 2000). Briefly, histological slides, 4 µm in thickness, were deparaffinized in xylene and a graded ethanol series, and antigen retrieval was achieved by heating in Cytomation Target Retrieval solution (DAKO Cytomation, Glostrup, Denmark) for 10 min in a microwave oven.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF‐R3, also known as Flt4, is specifically expressed by lymphatic, but not blood vascular endothelium in most normal tissues (Kaipainen et al, 1995; Partanen et al, 2000). However, there have been observations that VEGF‐R3 becomes re‐expressed by activated blood vascular endothelial cells associated with tumor growth and tissue repair (Partanen et al, 1999; Valtola et al, 1999; Kubo et al, 2000; Paavonen et al, 2000). Thus, VEGF‐R3 does not appear to represent a reliable marker for tumor‐associated lymphatics.…”
Section: New Growth Factors and Markers For Lymphatic Endotheliummentioning
confidence: 99%